A decision-making framework for seismic risk assessment in gas distribution networks: a case study of Tehran, Iran - Khoshnoud, Amin; Tayaran, Shahrzad; Ehsanifar, Mohammad; Mazaheri, Hossein (Frontiers in Built Environment, 2025)
IntroductionThe seismic vulnerability of urban critical infrastructure presents significant challenges for disaster preparedness and risk management. This study investigates the seismic risks associated with Pressure Reduction Stations (PRS) in Tehran, Iran.MethodsAn integrated decision-making framework combining Geographic Information Systems (GIS), Dominance-Based Decision-Making (DBDM), and Density-Based Spatial Clustering of Applications with Noise (DBSCAN) was used. Risk factors such as fault line proximity, ground motion, structural integrity, and population density were analyzed.ResultsHigh-risk zones and outlier PRS facilities were identified. Districts 2 and 10 were determined to be the most vulnerable. PRS-26 and PRS-10 were prioritized for retrofitting. The framework enabled robust spatial and probabilistic assessments.DiscussionThe integration of GIS, DBDM, and DBSCAN enhances the ability to identify seismic risk hotspots. This approach provides practical guidance for urban planners to improve resilience and disaster risk management for gas distribution infrastructure.